PARADIGMA MEMBANGUN GENERASI EMAS INDONESIA TAHUN 2045 - Antonius Remigius Abi (Universitas Negeri Malang, 2017)
Abstract: In 2045 Indonesia will enter the golden generation. It requires Indonesia to prepare its young generation ready to face the moment well so that gold generation become tough and think forward but always hold firmly Pancasila values. The 2045 gold generation is the hope of the Indonesian nation future. Education is a very central medium in preparing the gold generation, especially its character. The character that must be built must be holistic and comprehensive based on Pancasila. Education not only transfers knowledge but also values primarily character. Characters implanted in the golden generation must be based on three aspects namely the value of honesty, the value of truth and the value of justiceAbstrak: Tahun 2045 Indonesia memasuki generasi emas. Hal tersebut menuntut Indonesia untuk mempersiapkan generasi mudanya siap menghadapi momen tersebut dengan baik, sehingga generasi emas menjadi tangguh dan berfikir maju akan tetapi selalu memegang teguh nilai-nilai Pancasila. Generasi emas 2045 merupakan harapan masa depan bangsa Indonesia. Pendidikan merupakan media yang sangat sentral dalam mempersiapkan generasi emas terutama karakternya. Karakter yang harus dibangun haruslah bersifat holistik dan komprehensif berbasis pancasilais. Pendidikan tidak hanya mentransfer ilmu tetapi juga nilai-nilai terutama karakter. Karakter yang ditanamkan pada diri generasi emas haruslah berbasis tiga aspek yakni nilai kejujuran, nilai kebenaran dan nilai keadilan DOI : http://dx.doi.org/10.17977/um019v2i22017p085